Intentions to move abroad among medical students: a cross-sectional study to investigate determinants and opinions - Martella, Manuela; Lo Moro, Giuseppina; Scaioli, Giacomo; Grisafi-Schittone, Caterina; Gebbia, Gabriele; Siliquini, Roberta; Bert, Fabrizio (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim. The lack of health professionals and the physicians’ migration trend represents a challenging issue for the health systems’ sustainability worldwide. The current study aims to evaluate the intentions of Italian medical students to pursue their own careers abroad by investigating the push and pull factors of migration. Subject and Methods. A cross-sectional study was performed among Italian medical students through a self-administered que- stionnaire. Primary and secondary outcomes were established as the intention of moving abroad after graduation and knowledge about residency programmes, application, quality training and remuneration in the country of interest. Descriptive analysis for all variables and univariable and multivariable regression for primary and secondary outcomes were performed. Results. Overall, 307 medical students took part in the study. More than half of the sample considered moving abroad after gra- duation, mainly to find a higher quality training programme. Regression analysis highlighted a significant association between the primary outcome and general personal and professional reasons, as well as previous experiences abroad, whereas bureaucratic procedures were perceived as the main barrier. Perceived better knowledge about residency programmes and quality of training related to sources of information such as the Internet (blogs, forums, websites) and medical associations. Conclusion. Retention policies are necessary to meet the expectations and requests of future generations of doctors by allocating financial resources to offer high-quality training and broad career opportunities, together with appropriate wages, as crucial factors for discouraging the migration of healthcare professionals.